Experiences and Strategies of Learning Process Resilience of Undergraduate Nursing Students during the Covid-19 Pandemic in Bali: A Qualitative Content Analysis - Raya, Nyoman Agus Jagat; Sawitri, Ni Komang Ari; Karin, Putu Ayu Emmy Savitri (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: Resilience in a learning process during the Covid-19 pandemic is a distinct experience and challenge, thus, a resilience strategy is needed. This study aims to explore the experiences and strategies for resilience in the learning process of undergraduate nursing students during the Covid-19 pandemic in Bali.Method: This study is cross-sectional with an exploratory qualitative approach. A purposive sampling technique was applied to recruit the participants from July to September 2022, with the criteria that they had been undergoing the learning process for a minimum of one semester during the Covid-19 pandemic. There were 24 participants from five nursing education institutions in Bali. They were interviewed to gain data saturation. The data from in-depth verbal, non-verbal interviews, and other supporting documents were analyzed using qualitative content analysis.Results: There were 4 themes, 14 categories, and 52 codes emerging during the analysis. The experiences of the participants included the learning process and the problems faced during the Covid-19 pandemic such as physical, psychological, and social problems. Meanwhile, the resilience strategies were carried out with internal motivation, external motivation, independent learning, doing hobbies, and taking a rest.Conclusions: This study illustrated that resilience strategies were needed to achieve the goal of nursing learning. Nursing education institutions can potentially create innovations in nursing learning methods that are more communicative and interactive to minimize physical, psychological, and social problems, especially in the learning process during the pandemic transition to the Covid-19 endemic.